2022
DOI: 10.3389/fgene.2022.957251
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale differences in eukaryotic communities inside and outside salmon aquaculture cages revealed by eDNA metabarcoding

Abstract: Aquaculture impacts on marine benthic ecosystems are widely recognized and monitored. However, little is known about the community changes occurring in the water masses surrounding aquaculture sites. In the present study, we studied the eukaryotic communities inside and outside salmonid aquaculture cages through time to assess the community changes in the neighbouring waters of the farm. Water samples were taken biweekly over five months during the production phase from inside the cages and from nearby points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Many studies have now confirmed the strengths of eDNA metabarcoding for local detection of species and, thus community composition inference (Hansen et al, 2018). Similarly to analogous studies (Cilleros et al, 2019; Fraija‐Fernández et al, 2020; Jeunen, Knapp, et al, 2019; Jo et al, 2019; Larson et al, 2022; Li et al, 2021; Turon et al, 2022), our eDNA metabarcoding study confirm that fish community composition and biodiversity patterns can be reliably estimated using this approach.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have now confirmed the strengths of eDNA metabarcoding for local detection of species and, thus community composition inference (Hansen et al, 2018). Similarly to analogous studies (Cilleros et al, 2019; Fraija‐Fernández et al, 2020; Jeunen, Knapp, et al, 2019; Jo et al, 2019; Larson et al, 2022; Li et al, 2021; Turon et al, 2022), our eDNA metabarcoding study confirm that fish community composition and biodiversity patterns can be reliably estimated using this approach.…”
Section: Discussionsupporting
confidence: 88%
“…Custom demultiplexing of internal and external barcodes was undertaken using a combination of flexbar (Dodt et al, 2012; Renaud et al, 2015) and deML (Renaud et al, 2015). Operational taxonomic units OTUs were identified and assigned to taxonomy from demultiplexed samples using the MJOLNIR pipeline (https://github.com/uit-metabarcoding/MJOLNIR) as in (Turon et al, 2022). MJOLNIR implements a variety of programs from the OBITOOLS package (Boyer et al, 2016) for sequence preprocessing and taxonomic assignment as well as VSEARCH (Rognes et al, 2016) and SWARM (Mahé et al, 2022) for chimera detection and OTU clustering respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These investigations consistently found evidence that benthic microbial diversity, as measured from eDNA metabarcoding of bacteria and other organisms, is inversely related to organic enrichment and other impacts from aquaculture. Another investigation used eDNA metabarcoding to assess the eukaryotic communities within salmon pens off the coast or Norway relative to the nearby marine environment (Turon et al 2022). In contrast to observed trends in benthic microbial diversity, researchers found evidence that eukaryotic eDNA diversity was higher in water samples collected within salmon pens relative to those collected outside.…”
Section: Monitoring Health Of Salmon and Salmon Habitatmentioning
confidence: 99%
“…In contrast to observed trends in benthic microbial diversity, researchers found evidence that eukaryotic eDNA diversity was higher in water samples collected within salmon pens relative to those collected outside. This finding was attributed, at least partially, to the colonization of aquaculture structures by various taxa, such as brown algae and jellyfish (Turon et al 2022).…”
Section: Monitoring Health Of Salmon and Salmon Habitatmentioning
confidence: 99%